Business Strategy at The Integrated Service Point - Simona JACULJAKOVA; Katarina REPKOVA STOFKOVA; Dominik LAITKEP; Peter JUCHA (Communications of International Proceedings, 2021)
The strategy of modern business is very important because of the development of goods and services offered by individual business entities to increase the demand for the goods or services for a given customer. As part of developing a modern business strategy in the postal sector, we focused on the Integrated Service Point, which is provided by the national postal operator. In the given point of the Integrated Service Point (ISP), we focused on providing new approaches that are not only part of the economy of modern business but also part of the support of competitiveness in the postal sector. We defined terms such as modern business strategy, e-Government, integrated service point together with the definition of current services of this workplace. In the practical part of the article, we carried out primary research, which was focused for obtaining information from customers of the Integrated Service Point in the Žilina Self-Governing Region, when we found out which one of new approaches would be adopted by customers in the given work place. After conducting the primary research, we found that individual customers would receive services such as Convert Document from E-mail Box, Image from Cadastral Map, etc. After a detailed analysis, we found a new service, the Cadastral Map Image, would be feasible. The integration of the proposed service could lead to reach new customers, better competitiveness of the national postal operator, as well as the development of a modern business in the postal sector.
Keywords: Postal Service; E-Government; Integrated Service Point; Modern Business Strategy